A catalyst, its preparation method and application in the preparation of pentyl cyanide by ammoniating and dehydrogenating pentanol

CN122955480APending Publication Date: 2026-10-23DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510486683.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

该工艺是釜式间歇加氢工艺,在加氢前为防止催化剂“中毒”,需要对原料戊烯腈进行碱洗和水洗工段处理以洗脱其中的CN-离子,而洗脱产生的含CN-离子的废水后续的生化处理成本极高,而且污染环境

Benefits of technology

[0044]本发明涉及的戊醇氨化脱氢合成戊腈的反应工艺相比于氰化钠法、戊烯腈加氢法,合成原料为醇和氨,原料易得,而且副产物只有氢气和水,对环境友好,生产安全。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005364365320000051
    Figure BDA0005364365320000051
  • Figure BDA0005364365320000052
    Figure BDA0005364365320000052
  • Figure BDA0005364365320000053
    Figure BDA0005364365320000053
Patent Text Reader

Abstract

The application discloses a catalyst and a preparation method and application thereof in the preparation of pentyl cyanide through the ammoniation dehydrogenation of pentanol, and belongs to the field of catalysts. The catalyst comprises an active component and a carrier; the active component is selected from tin oxide, and the carrier is selected from aluminum oxide. The mass of the active component is 5-30% wt of the mass of the catalyst, calculated in terms of the mass of tin element. The preparation method comprises the following steps: kneading and forming aluminum oxide, drying and calcining to obtain an aluminum oxide carrier, impregnating the carrier in a solution containing a tin precursor, and drying and calcining to obtain the catalyst. The catalyst prepared by the application has the advantages of high activity, high selectivity of pentyl cyanide and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a catalyst, its preparation method, and its application in the amination and dehydrogenation of pentanol to pentanilon, belonging to the field of catalysts. Background Technology

[0002] n-Valononitrile, also known as n-butyl cyanide, butyl cyanide, or butane cyanide, is a colorless liquid at room temperature. It is miscible with ethanol and ether, but insoluble in water. N-Valononitrile is mainly used to synthesize 2-butyl-5-chloro-1H-imidazol-4-carboxaldehyde, an intermediate in the synthesis of losartan, a sartan drug used to treat hypertension.

[0003] Traditional industrial processes for synthesizing n-pentadienyl nitrile include the sodium cyanide method and the pentadienyl nitrile hydrogenation method. The reaction equation for the sodium cyanide method is:

[0004] CH3-CH2-CH2-CH2Cl+NaCN=CH3-CH2-CH2-CH2-CN+NaCl.

[0005] This method requires the use of highly toxic sodium cyanide, which not only causes severe environmental pollution but also has high costs for its raw materials, 1-chlorobutane and sodium cyanide, as well as subsequent separation and purification. The reaction equation for the pentenoylenide hydrogenation process is as follows:

[0006] CH3-CH2-CH=CH-CN+H2=CH3-CH2-CH2-CH2-CN.

[0007] This method uses pentenonitrile (2-PN), a byproduct intermediate of adiponitrile, as a synthetic raw material, and then hydrogenates pentenonitrile to obtain n-pentenonitrile. This process is a batch hydrogenation process using a stirred tank. Before hydrogenation, to prevent catalyst poisoning, the pentenonitrile raw material needs to undergo alkaline washing and water washing to remove CN. - Ions, and the CN-containing ions produced by elution - The subsequent biochemical treatment of ion-containing wastewater is extremely costly and pollutes the environment.

[0008] Du Qian et al. (Fine and Specialty Chemicals, 2018, 26:15-17) reported that the optimal reaction conditions for preparing n-valeronitrile using 1-chlorobutane and sodium cyanide as raw materials and tetrabutylammonium chloride as catalyst were: n(1-chlorobutane):n(sodium cyanide) = 1:1.10, the amount of tetrabutylammonium chloride catalyst was 8% of the mass of 1-chlorobutane, the reaction was carried out at 90℃ for 4 hours, and after the reaction was completed, the temperature was lowered to room temperature, and the n-valeronitrile product was obtained by separation, washing with water and vacuum distillation. The conversion rate of 1-chlorobutane reached 96.56%.

[0009] Jin Shuhan et al. (Chemical Technology and Development, 2017, 46(4):13-16) reported a method for synthesizing n-pentanol by one-step amination and dehydrogenation of n-pentanol. The catalyst used was a Cu / SiO2 type supported catalyst, with a pentanol conversion rate of up to 99.23% and a pentanol selectivity of up to 99.31%.

[0010] Zhu He reported (Study on the Two-Step Synthesis of Fatty Amines from Fatty Alcohols, Master's Thesis, Hebei University of Technology, 2020) that FeZn / gama-Al2O3 was used for the dehydrogenation amination of n-pentanol to synthesize n-pentanilide. Optimized process conditions were obtained through systematic investigation: atmospheric pressure, ammonia-to-pentanol molar ratio of 3.5:1, residence time of 13 s, and reaction temperature of 390℃. Under these conditions, the conversion of n-pentanol was 100%, and the yield of n-pentanilide was 89.55%. The stability of the FeZn / gama-Al2O3 catalyst was investigated. After more than 40 h of use, the conversion of n-pentanol and the yield of n-pentanilide decreased to 95.24% and 78.23%, respectively, possibly due to carbon buildup at high temperatures leading to reduced catalyst activity. The catalyst activity was restored after re-calcination at high temperature. This catalyst also showed good catalytic performance in other reactions involving the dehydrogenation amination of fatty alcohols to synthesize the corresponding nitriles.

[0011] Patent (CN111036268B) discloses an alumina composite material, its preparation method, application, and a method for synthesizing pentanolytes. The alumina composite material is mainly composed of alumina and a supported carbon material, wherein the supported carbon material includes nitrogen-doped carbon material and transition metal oxides supported on the nitrogen-doped carbon material. In the above-mentioned alumina composite material, the transition metal oxides serve as the dehydrogenation active component, and the alumina serves as the ammoniation active component. The transition metal oxides are supported on the nitrogen-doped carbon material and form a complex with the alumina. Therefore, the transition metal and alumina, as catalytically active components, exhibit better catalytic performance and stability, resulting in higher conversion rates, selectivity, and stability when used to catalyze the ammoniation and dehydrogenation of pentanol to synthesize nitriles. Summary of the Invention

[0012] This application aims to develop a highly active and selective Sn / Al catalyst for the ammoniation and dehydrogenation of pentanol to pentanilide. This is the first report of the use of this catalyst for the ammoniation and dehydrogenation of pentanol to pentanilide.

[0013] According to a first aspect of this application, a catalyst is provided for the amination and dehydrogenation of pentanol to produce pentanilide.

[0014] A catalyst comprising an active component and a support;

[0015] The active component is selected from tin oxide;

[0016] The carrier is selected from alumina.

[0017] Optionally, the mass of the active component is 5 to 30% wt of the catalyst mass; the mass of the active component is based on the mass of tin in tin oxide.

[0018] Optionally, the mass of tin is independently selected from any value of 5% wt., 10% wt., 15 wt.%, 20% wt., 25% wt., 30% wt., or a range between any two of the above.

[0019] The carrier is aluminum oxide;

[0020] The carrier is formed by kneading alumina.

[0021] The carrier is dried and calcined.

[0022] According to a second aspect of this application, a method for preparing the above-mentioned catalyst is provided. Alumina is kneaded and shaped, dried, and calcined to obtain an alumina support. The support is then immersed in a solution containing a tin precursor, dried, and calcined to obtain the catalyst.

[0023] The method for preparing the catalyst described above includes at least the following steps:

[0024] The catalyst is obtained by immersing an alumina support in a solution containing a tin precursor, drying and calcining it.

[0025] Optionally, the impregnation is a vacuum equal-volume impregnation;

[0026] The soaking time is 1 to 2 hours.

[0027] Optionally, the tin precursor is selected from stannous chloride and / or stannous chloride.

[0028] Optionally, the solution containing the tin precursor contains a solvent selected from ethanol.

[0029] Optionally, the drying temperature is selected from 110 to 130°C, and the drying time is 4 to 8 hours.

[0030] Optionally, the roasting temperature is selected from 600 to 800°C, and the roasting time is 2 to 4 hours.

[0031] Optionally, the method for preparing the alumina support includes: kneading and extruding alumina and dilute nitric acid into strips, drying, and calcining to obtain the alumina support.

[0032] According to a third aspect of this application, a method for producing pentanilide by ammoniation and dehydrogenation of pentanol is provided. This catalyst possesses advantages such as high activity, high pentanilide selectivity, and high stability.

[0033] A method for producing pentanolyte by amination and dehydrogenation of pentanol includes at least the following steps:

[0034] The raw materials containing pentanol and ammonia are mixed, contacted with a catalyst, and reacted to obtain a product containing pentanilide.

[0035] The catalyst is selected from the catalysts described above or the catalysts prepared by the methods described above.

[0036] Optionally, the molar ratio of ammonia to pentanol is 2 to 6.

[0037] Optionally, the molar ratio of ammonia to pentanol is any value among 2, 3, 4, 5, and 6, or a range between two values.

[0038] Optionally, the mass hourly space velocity (WHSV) of the pentanol is 0.1–0.5 h⁻¹. -1 .

[0039] Optionally, the mass hourly space velocity (WHSV) of the pentanol is 0.1 h⁻¹. -1 0.2h -1 0.3h -1 0.4h -1 0.5h -1 Any value in the range or between two values.

[0040] Optionally, the reaction pressure is 0.1–0.3 MPa, and the reaction temperature is 380–480 °C.

[0041] Optionally, the pressure of the reaction is selected from any value of 0.1 MPa, 0.2 MPa, 0.3 MPa, or a range between two values.

[0042] Optionally, the temperature of the reaction is selected from any value or a range between two values ​​of 380°C, 400°C, 420°C, 440°C, 460°C, and 480°C.

[0043] The beneficial effects that this application can produce include:

[0044] Compared to the sodium cyanide method and the pentenyl nitrile hydrogenation method, the reaction process for synthesizing pentenyl nitrile by ammoniation and dehydrogenation of pentanol involved in this invention uses alcohol and ammonia as raw materials, which are readily available, and the only byproducts are hydrogen and water, making it environmentally friendly and safe to produce.

[0045] Because the relative volatility of alcohols and the corresponding nitrile compounds produced are similar, the conversion rate of the alcohol-to-nitrile amination-dehydrogenation reaction is low, making the separation of unconverted alcohols and the generated nitrile compounds difficult. The catalyst used in this invention catalyzes the alcohol-to-nitrile amination-dehydrogenation reaction, achieving a very high conversion rate (over 99.0%), thus eliminating the problem of difficult separation of alcohols and nitriles.

[0046] The catalyst prepared by this invention can be applied to the process of pentanol amination and dehydrogenation to pentanilide. This catalyst has the advantages of high pentanol conversion, high pentanilide selectivity and high stability. Compared with conventional FeZn-based catalysts, tin is inexpensive and readily available, and the catalyst price is low. Detailed Implementation

[0047] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0048] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.

[0049] Unless otherwise specified, all test methods are standard and all instrument settings are those recommended by the manufacturer.

[0050] The analysis method in the embodiments of this application is as follows:

[0051] The products were analyzed using an Agilent 7890B gas chromatograph.

[0052] In the embodiments of this application, the catalyst activity evaluation indicators, namely pentanol conversion rate, ammonia conversion rate, and pentadiene selectivity, are all calculated based on mass:

[0053] Pentanol conversion rate:

[0054]

[0055] Ammonia conversion rate:

[0056]

[0057] valerate selectivity:

[0058]

[0059] In the above formula, m represents mass.

[0060] Comparative Example 1

[0061] Alumina and dilute nitric acid (2% wt) were mixed, kneaded, and extruded into strips, dried at 120°C, and calcined at 550°C for 3 hours to obtain an alumina carrier.

[0062] According to the content of the active components iron and zinc, a certain amount of Fe(NO3)3·9H2O and Zn(NO3)2·6H2O (weight ratio of 4 / 1) were weighed and dissolved in ethanol solution. Alumina was placed in a sealed container, and the impregnation solution was drawn into the carrier using a vacuum equal-volume impregnation method with a vacuum degree less than 10 Pa. Then, it was impregnated at room temperature for 2 hours, dried at 120℃ for 6 hours, and calcined at 700℃ for 3 hours. The resulting catalyst Cat-A contained 13% wt iron and 7% wt Zn. 。

[0063] Example 1

[0064] Alumina and dilute nitric acid (2% wt) were mixed, kneaded, and extruded into strips, dried at 120°C, and calcined at 550°C for 3 hours to obtain an alumina carrier.

[0065] According to the tin content of the active component, a certain amount of SnCl2 was weighed and dissolved in an ethanol solution. Alumina was placed in a sealed container, and the impregnation solution was drawn into the carrier using a vacuum equal-volume impregnation method. The vacuum degree was less than 10 Pa. Then, it was impregnated at room temperature for 2 hours, dried at 120℃ for 6 hours, and calcined at 700℃ for 3 hours. The obtained catalyst Cat-B contained 20% wt% tin.

[0066] Example 2

[0067] Alumina and dilute nitric acid (2% wt) were mixed, kneaded, and extruded into strips, dried at 120°C, and calcined at 550°C for 3 hours to obtain an alumina carrier.

[0068] According to the tin content of the active component, a certain amount of SnCl4 was weighed and dissolved in an ethanol solution. Alumina was placed in a sealed container, and the impregnation solution was drawn into the carrier using a vacuum equal-volume impregnation method with a vacuum degree of less than 10 Pa. Then, it was impregnated at room temperature for 1 hour, dried at 110℃ for 8 hours, and calcined at 600℃ for 4 hours. The obtained catalyst Cat-C contained 5% wt tin.

[0069] Example 3

[0070] Alumina and dilute nitric acid (2% wt) were mixed, kneaded, and extruded into strips, dried at 120°C, and calcined at 550°C for 3 hours to obtain an alumina carrier.

[0071] According to the tin content of the active component, a certain amount of SnCl2 and SnCl4 (weight ratio 1 / 1) were weighed and dissolved in ethanol solution, and placed in a sealed container. Alumina was placed in the sealed container, and the impregnation solution was drawn into the carrier using a vacuum equal-volume impregnation method with a vacuum degree of less than 10 Pa. Then, it was impregnated at room temperature for 1 hour, dried at 130℃ for 4 hours, and calcined at 800℃ for 2 hours. The obtained catalyst Cat-D contained 30% wt% tin.

[0072] Example 4

[0073] Alumina and dilute nitric acid (2% wt) were mixed, kneaded, and extruded into strips, dried at 110°C, and calcined at 600°C for 3 hours to obtain an alumina carrier.

[0074] According to the tin content of the active component, a certain amount of SnCl2 was weighed and dissolved in an ethanol solution. Alumina was placed in a sealed container, and the impregnation solution was drawn into the carrier using a vacuum equal-volume impregnation method. The vacuum degree was less than 10 Pa. Then, it was impregnated at room temperature for 2 hours, dried at 125℃ for 7 hours, and calcined at 750℃ for 3 hours. The tin content in the obtained catalyst Cat-E was 15% wt.

[0075] Example 5

[0076] The performance of the catalyst Cat-A prepared in Comparative Example 1 for the dehydrogenation and amination of pentanol to pentanilide was evaluated in a reaction apparatus. The reactor diameter was 14 mm, the catalyst loading was 4 g, and the temperature was increased to 420 °C at a rate of 10 °C / min under a nitrogen atmosphere. Pentanol and ammonia were introduced, and the evaluation times were 74 h and 120 h, respectively. The reaction conditions were: temperature 420 °C, pressure 0.1 MPa, and pentanol mass hourly space velocity (HHSV) 0.25 h⁻¹. -1 The molar ratio of ammonia to pentanol was 6:1. The product was analyzed using an Agilent 7890B GC, and the specific evaluation results are shown in Table 1.

[0077] Example 6

[0078] The performance of the catalyst Cat-B prepared in Example 1 for the dehydrogenation and amination of pentanol to pentanilide was evaluated in a reaction apparatus. The reactor diameter was 14 mm, the catalyst loading was 4 g, and the temperature was increased to 420 °C at a rate of 10 °C / min under a nitrogen atmosphere. Pentanol and ammonia were introduced, and the evaluation times were 74 h and 120 h, respectively. The reaction conditions were: temperature 420 °C, pressure 0.1 MPa, and pentanol mass hourly space velocity (HHSV) 0.25 h⁻¹. -1 The molar ratio of ammonia to pentanol was 6:1. The product was analyzed using an Agilent 7890B GC, and the specific evaluation results are shown in Table 1.

[0079] Example 7

[0080] The performance of the Cat-C catalyst prepared in Example 2 for the dehydrogenation and ammoniaation of pentanol to pentanilide was evaluated in a reaction apparatus. The reactor diameter was 14 mm, the catalyst loading was 4 g, and the temperature was increased to 430 °C at a rate of 10 °C / min under a nitrogen atmosphere. Pentanol and ammonia were introduced, and the evaluation time was 200 h. The reaction conditions were: temperature 430 °C, pressure 0.1 MPa, and pentanol mass hourly space velocity (HHSV) 0.50 h⁻¹. -1 The molar ratio of ammonia to pentanol was 6:1. The product was analyzed using an Agilent 7890B GC, and the specific evaluation results are shown in Table 1.

[0081] Example 8

[0082] The performance of the Cat-D catalyst prepared in Example 3 for the dehydrogenation and ammoniaation of pentanol to pentanilide was evaluated in a reaction apparatus. The reactor diameter was 14 mm, the catalyst loading was 4 g, and the temperature was increased to 380 °C at a rate of 10 °C / min under a nitrogen atmosphere. Pentanol and ammonia were introduced, and the evaluation time was 100 h. The reaction conditions were: temperature 380 °C, pressure 0.1 MPa, and pentanol mass hourly space velocity (WHSV) 0.10 h⁻¹. -1 The molar ratio of ammonia to pentanol was 2:1. The product was analyzed using an Agilent 7890B GC, and the specific evaluation results are shown in Table 1.

[0083] Example 9

[0084] The performance of the Cat-D catalyst prepared in Example 3 for the dehydrogenation and ammoniaation of pentanol to pentanilide was evaluated in a reaction apparatus. The reactor diameter was 14 mm, the catalyst loading was 4 g, and the temperature was increased to 420 °C at a rate of 10 °C / min under a nitrogen atmosphere. Pentanol and ammonia were introduced, and the evaluation time was 500 h. The reaction conditions were: temperature 420 °C, pressure 0.1 MPa, and pentanol mass hourly space velocity (HHSV) 0.25 h⁻¹. -1 The molar ratio of ammonia to pentanol was 6:1. The product was analyzed using an Agilent 7890B GC, and the specific evaluation results are shown in Table 1.

[0085] Example 10

[0086] The performance of the Cat-E catalyst prepared in Example 4 for the dehydrogenation and ammoniaation of pentanol to pentanilide was evaluated in a reaction apparatus. The reactor diameter was 14 mm, the catalyst loading was 4 g, and the temperature was increased to 480 °C at a rate of 10 °C / min under a nitrogen atmosphere. Pentanol and ammonia were introduced, and the evaluation time was 120 h. The reaction conditions were: temperature 480 °C, pressure 0.3 MPa, and pentanol mass hourly space velocity (HHSV) 0.30 h⁻¹. -1 The molar ratio of ammonia to pentanol was 4:1. The product was analyzed using an Agilent 7890B GC, and the specific evaluation results are shown in Table 1.

[0087] Table 1 Catalyst Reaction Performance

[0088]

[0089] The experimental results in Table 1 show that, compared with the iron and zinc catalysts supported on alumina (Cat-A), the tin-based catalyst supported on alumina (Cat-B) has higher pentanol conversion and pentanilide selectivity, and significant stability advantages. Under the reaction conditions investigated, the prepared Cat-C, Cat-D and Cat-E catalysts exhibit high activity, pentanilide selectivity and stability.

[0090] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A catalyst, characterized in that, Includes active components and carriers; The active component is selected from tin oxide; The carrier is selected from alumina.

2. The catalyst according to claim 1, characterized in that, The mass of the active component is 5 to 30% wt of the catalyst mass; the mass of the active component is based on the mass of tin in tin oxide.

3. The method for preparing the catalyst according to claim 1 or 2, characterized in that, At least the following steps are included: The catalyst is obtained by immersing an alumina support in a solution containing a tin precursor, drying and calcining it.

4. The preparation method according to claim 3, characterized in that, The impregnation is a vacuum equal-volume impregnation; The soaking time is 1 to 2 hours.

5. The preparation method according to claim 3, characterized in that, The tin precursor is selected from stannous chloride and / or stannous chloride; The solution containing the tin precursor contains a solvent selected from ethanol.

6. The preparation method according to claim 3, characterized in that, The drying temperature is 110–130°C; The drying time is 4 to 8 hours.

7. The preparation method according to claim 3, characterized in that, The roasting temperature is 600–800°C; The roasting time is 2 to 4 hours.

8. A method for producing pentanilide by ammoniation and dehydrogenation of pentanol, characterized in that, At least the following steps are included: The raw materials containing pentanol and ammonia are mixed, contacted with a catalyst, and reacted to obtain a product containing pentanilide. The catalyst is selected from the catalyst described in claim 1 or 2, or the catalyst prepared by the preparation method described in any one of claims 3 to 7.

9. The method according to claim 7, characterized in that, The molar ratio of ammonia to pentanol is 6 to 2; The mass hourly space velocity (MSV) of the pentanol is 0.1–0.5 h⁻¹. -1 ; The reaction pressure is 0.1–0.3 MPa; The reaction temperature is 380–480°C.

Citation Information

Patent Citations

  • Alumina composite materials, their preparation methods, applications, and the synthesis method of n-valeronitrile

    CN111036268B